Peran viral marketing TikTok dan kepercayaan pelanggan dalam membentuk niat beli konsumen: Studi kasus Latar Ombo Coffee di Kudus - Adriyanto, Mohamad Seva; Kusuma, Aryanti Muhtar (Nur Science Institute, 2026)
This study aims to analyze the influence of TikTok social media strategies (via viral marketing) and customer trust on consumer purchase intention at Latar Ombo Coffee in Kudus Regency. Employing a quantitative approach, this research involved 134 respondents selected through a purposive sampling method, with criteria including active TikTok users familiar with the Latar Ombo Coffee brand. Data collection was conducted online using Google Forms. The data analysis technique utilized Structural Equation Modeling (SEM), facilitated by SmartPLS 4 software. The results indicate that viral marketing on TikTok has a positive and significant influence on purchase intention, suggesting that creative and organic content effectively attracts potential customers' attention. Furthermore, customer trust was also proven to have a positive and significant impact on purchase intention, reinforcing that brand credibility is a key factor in consumer decision-making. Overall, the integration of engaging digital promotion and trust-building is crucial in increasing sales conversion within the coffee industry. The author expresses gratitude to the management of Latar Ombo Coffee and all respondents for their valuable contributions to this study.